Upaya Meningkatkan Hasil Belajar Matematika Materi Keliling dan Luas Lingkaran Pada Peserta Didik Melalui Metode Diskusi di Kelas IV SDN 156/X Tanjung Solok Semester Ganjil Tahun Ajaran 2021/2022 - Nuraini Nuraini (Journal on Education, 2022)
This study aims to describe and obtain information on improving mathematics learning outcomes through the discussion method. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were the fourths’ grade students of SDN 156/X Tanjung Solok, totaling 5 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that the discussion method could improve the mathematics learning outcomes of fourth grade students at SDN 156/X Tanjung Solok by giving rewards.